Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In the proof of theorem 3.1 they put : $\langle X,\nabla f \rangle =X(f)$ after that they say that: for a curve $c$ on $M$ then $\left\langle\dfrac{\mathrm{d}c}{\mathrm{d}t},\nabla f\right\rangle=\dfrac{\mathrm{d}(f\circ c)}{\mathrm{d}t}$

enter image description here

i don't understand why $<X,\nabla f > =1$ ?


Thank you .

share|cite|improve this question

$$\dfrac{dc}{dt}=\left(\dfrac{dc^1}{dt}, \dfrac{dc^2}{dt}, \dots , \dfrac{dc^n}{dt}\right)$$ $$\nabla f=\left(\dfrac{\partial f}{\partial x^1}, \dfrac{\partial f}{\partial x^2}, \dots , \dfrac{\partial f}{\partial x^n}\right)$$ Also, we have: $$\dfrac{d(f\circ c)}{dt}=\dfrac{df(c^1(t),c^2(t),\dots ,c^n(t))}{dt}=\dfrac{\partial f}{\partial x^1}\dfrac{dc^1}{dt}+\dots+\dfrac{\partial f}{\partial x^n}\dfrac{dc^n}{dt}=\left\langle\dfrac{dc}{dt},\nabla f\right\rangle$$

share|cite|improve this answer
from the definition $\displaystyle<\frac{dc}{dt},\nabla f>=\frac{dc}{dt}(f)$ why $\displaystyle<\frac{dc}{dt},\nabla f>=\frac{d(f\circ c)}{dt}$ – Vrouvrou Apr 20 '13 at 6:03
How do you define $X$? Above I wrote it like a vector , however it is more than a vector of $\mathbb R ^n$. If you write it in the base : $$X=\chi^1\dfrac{\partial}{\partial x^1}+\dots+\chi^n\dfrac{\partial}{\partial x^n}$$ So $$\dfrac{dc}{dt}=\dfrac{dc^1}{dt}\dfrac{\partial}{\partial x^1}+\dots+\dfrac{dc^n}{dt}\dfrac{\partial}{\partial x^n}$$ Apply $f$ , and you obtain: $$\dfrac{dc}{dt}(f)=\dfrac{dc^1}{dt}\dfrac{\partial f}{\partial x^1}+\dots+\dfrac{dc^n}{dt}\dfrac{\partial f}{\partial x^n}$$ – Dimitrios Nt Apr 20 '13 at 7:27
ok ,thank you i edited my question can you help me ? – Vrouvrou Apr 20 '13 at 18:15
$\langle X, grad f \rangle= \langle \rho\cdot grad f, grad f\rangle=\rho \langle grad f , grad f \rangle= \dfrac{1}{\langle grad f,grad f \rangle}\langle grad f,grad f \rangle=1 $ – Dimitrios Nt Apr 20 '13 at 23:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.